Digital hygiene crisis: why 73% of educational institutions are at risk in 2025 - Stoika Myroslav; Sztojka Miroszláv; Стойка Мирослав; Temető Ádám; Теметев Адам (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. What is digital hygiene and why it matters in 2025? Digital hygiene crisis poses a severe threat to educational institutions, with studies showing 73% risk of cybersecurity breaches by 2025. As schools become more digitally dependent, understanding digital hygiene - practices that maintain secure digital environments - is crucial. What is digital hygiene and why it matters in 2025? "Learners in the internet age don't need more information. They need to know how to efficiently use the massive amount of information available at their fingertips – to determine what's credible, what's relevant, and when it's useful to reference." — Anna Sabramowicz, eLearning designer and digital learning expert Digital hygiene encompasses proactive practices that institutions, staff, and students adopt to maintain online security and digital well-being. On May 2, 2025, countries began implementing formal approaches, including the Concept of Digital Hygiene for Preschoolers, aimed at creating safe digital infrastructure in schools [4]. Digital citizenship and cyber hygiene work together to create secure educational environments. While cyber hygiene focuses on technical safety practices, digital citizenship covers broader behavioral standards [5]. Schools lacking proper digital hygiene face significant risks, particularly regarding sensitive data protection [2]. Key impacts include: • Compromised sensitive information: Exposure of personal data [2] • Identity theft risks: Targeted attacks by cybercriminals [2] • Academic integrity issues: Unauthorized access can compromise academic records [2] • Significant reputational damage: Security breaches harm institutional reputation [1] • Financial and operational disruption: Data breaches cause financial losses [1] Poor digital hygiene can impact students' mental health through inappropriate content exposure. This risk is higher for younger students [6]. Core digital hygiene practices for educational institutions.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: digital hygiene; education institution